The judicial system and the competitiveness of services in the Superior Court of Justice of Huánuco 2016 - Alvarado-López, Luis C. (2019)
The problem "The judicial system and the competitiveness of services in the Superior Court of Justice of Huánuco", it is a problem of vital importance since it is the nucleus of the organization for the success or failure of the administration of justice. The objectives, determine the quality of services provided in the Superior Court of Justice. In addition, the methods, the hermeneutics, heuristics, random, analytical, dogmatics and sociological methods were used in their various contexts. With a sample of 30 respondents, whose answers and evidence reveal that services are deficient, so the clamor of users to improve services and not to harm users. It was worked this problem using the scientific method where the objectives were achieved, the research hypothesis and null.